2014
DOI: 10.1097/bsd.0b013e318299c6d8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Bioresorbable Self-reinforced Posterior Cervical Rods

Abstract: Copolymer rods have adequate shear resistance, but less load resistance and stiffness compared with titanium rods. Their stiffness is closer to that of bone, causing less stress shielding and better gradual dynamic loading. Their use in semirigid posterior stabilization of the cervical spine may be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…After an average of 18 months follow-up, there was no evidence of adjacent segment diseases in any of the cases. In contrast to traditional metallic implants, some polymer materials have biodegradable properties that allow the implant to degrade gradually over time [13,14]. The Young's modulus of the polymer rods was found to be closer to that of bone, and the lower stiffness of the rods meant less gradual dynamic loading and stress shielding of the fusion site.…”
Section: Introductionmentioning
confidence: 99%
“…After an average of 18 months follow-up, there was no evidence of adjacent segment diseases in any of the cases. In contrast to traditional metallic implants, some polymer materials have biodegradable properties that allow the implant to degrade gradually over time [13,14]. The Young's modulus of the polymer rods was found to be closer to that of bone, and the lower stiffness of the rods meant less gradual dynamic loading and stress shielding of the fusion site.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated how biodegradable implants may offer superior outcomes for lumbar spine fusion over conventional metal spinal implants, including a lower contact force at adjacent facet joints, lower peak stresses in the adjacent disc and greater loading on the anterior bone graft region. Savage et al [ 20 ] found that biodegradable rods produced less stress shielding and offered better dynamic loading in the spine over titanium rods. In addition to mechanical advantages, the radiolucent feature of resorbable rods could allow for better imaging and potentially eliminate surgical complications associated with removing metallic implants.…”
Section: Discussionmentioning
confidence: 99%
“…FE models of the biodegradable spinal rods (self-reinforced copolymer rod, Inion Oy, Tampere, Finland) [ 20 ] and titanium spinal rods were incorporated into the CB PROT II Posterior Spinal System (Chin Bone Corp., Taiwan; US FDA 510(k): K142655), which consists of titanium alloy screws (diameter 5.5 mm) connected by vertical rods. The lumbar intervertebral cage was modeled from the ReBorn Essence cage (Baui Biotech Co. Ltd., New Taipei City, Taiwan) made of PEEK.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent in vitro characterization study compared bioresorbable posterior cervical rods to commonly used Ti alloy rods. 41 The bioresorbable implants were shown to have adequate shear resistance but less load resistance and stiffness compared to the Ti rods. However, the stiffness of the bioresorbable rods (16.6-21.4 N/mm) was similar to bone, which resulted in better gradual dynamic loading.…”
Section: Bioabsorbablesmentioning
confidence: 99%